Improving basil productivity in coastal sandy soil Yogyakarta by balanced Urea-ZA (N-S) fertilizers and application of soil amendment to increase fertilization effectiveness - Cahyo Wulandari; Nasih Widya Yuwono; Yudhistira Galang Pravasta; Sri Lestari (Faculty of Agriculture, Universitas Gadjah Mada jointly with PISPI, 2023)
Basil is a plant that can be cultivated in Psamment (coastal sandy soil). Basil requires nitrogen (N) and sulfur (S), so the N-S balance is needed to obtain optimal results. Psamment contains low colloid, causing nutrients to be barely bound and easily lost. Zeolite and biochar can be a solution. This study aimed to determine the composition and frequency of fertilization, as well as the use of soil amendment for basil growth. This research consisted of two interrelated studies arranged in a Randomized Complete Block Design. The research was conducted in Bugel, Panjatan, Kulon Progo, and the analysis was performed at the Soil Department Laboratory, Faculty of Agriculture, Universitas Gadjah Mada. The first study consisted of two factors, namely Urea-ZA composition (0:0, 60:40, 70:30, 80:20, 90:10, and 100:0) and frequency of fertilization (every 1 and 2 weeks). The application of Urea-ZA (80:20) gave the best fresh-dry weight, N-S content, and N-S uptake of basil, and this result was used as the reference for the second study. The second study consisted of two factors, namely Urea-ZA fertilizer doses (50%, 75%, and 100%), and types and doses of soil amendment (without amendment, zeolite 7.5 t/ha, zeolite 15 t/ha; biochar 7.5 t/ha, and biochar 15 t/ha). It can be concluded that soil amendments application improved the chemical properties of psamment, fresh-dry weight, N-S content, and N-S uptake of basil. Furthermore, biochar and zeolite could increase the effectiveness of fertilization, so the dose of Urea-ZA fertilizer could be reduced until 50%.